Penatalaksanaan Diabetes Mellitus (DM) Secara Mandiri Dengan Buku Saku Terhadap Pengetahuan, Sikap, Dan Kadar Gula Darah - Siti Mulidah; Asrin Asrin; Ulfah Agus Sukrillah (JURNAL KEPERAWATAN MERSI, 2020)
Background: Diabetes mellitus (DM) is one of progressive chronic disease that attack million of people in the world. This disease is one significant cause of natality and mortality and also many complications accompany the patient. So, based on earlier study the educational program of DM that focus on self management is one good choice for developing in relating of increasing the quality of patient lifeMetode: The purpose of this study is to prove self management of DM by using pocket book toward knowledge, attitude, and the level of blood glucose. Type of this study is quasi experimental by using static pre and post test with control group design. The respondents were DM patients in area of Puskesmas II Sokaraja, Banyumas Regency. There were 40 respondents that were participated in this study. The knowledge and attitude of patients were measured by using pre and post test questioner. The level blood glucose was assessed by checking temporally blood glucose . Data analyse was used paired t test.Result: Majority of respondents education were primary school (SD and SMP) in range of 35 - 60 years old, majority of them were jobless, and duration of suffering from DM was short term dominantly. Pocket book of self DM management can increase knowledge of 17.4 point, attitude of 17.5 point and blood glucose of 17.45 point. Statistically, there was not effect of giving pocket book for self management of DM of knowledge (p = 0.07) and the level of blood glucose (p = 0.46). The pocket book of self management of DM was increase significantly of patients attitude (p = 0.00).Conclusion: Self management of DM by giving pocket book influence the attitude and the was not influence of knowledge and the level of blood glucose.